1997
DOI: 10.2166/wst.1997.0576
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of selected azo dyes under methanogenic conditions

Abstract: Biological treatment of wastewaters discharged by the textile industry could potentially be problematic due to the high toxicity and recalcitrance of the commonly-used azo dye compounds. In the present report, the fate of two azo dyes under methanogenic conditions was studied. Mordant Orange 1 (MO1) and Azodisalicylate (ADS) were completely reduced and decolorised in continuous UASB reactors in the presence of cosubstrates. In the MO1 reactor, both 5-aminosalicylic acid (5-ASA) and 1,4-phenylenediamine were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 0 publications
3
68
2
1
Order By: Relevance
“…Reactive Red 120 (before ozonation) after 22 days incubation (Fig. 5) can be attributed to the adaptation of bacteria to recalcitrant azo dye substrate or so called cross-acclimatization [4]. Krull et al (1998) reported that the biomass used for the anoxic treatment of six different reactive azo dyes was growing in the following aerobic phase when readily biodegradable compounds were present [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive Red 120 (before ozonation) after 22 days incubation (Fig. 5) can be attributed to the adaptation of bacteria to recalcitrant azo dye substrate or so called cross-acclimatization [4]. Krull et al (1998) reported that the biomass used for the anoxic treatment of six different reactive azo dyes was growing in the following aerobic phase when readily biodegradable compounds were present [31].…”
Section: Resultsmentioning
confidence: 99%
“…A significant remainder of about 40-70% of COD and color in textile finishing industry effluents after conventional biological treatment requires an advanced treatment for improving the quality [3][4][5][6]. Commercial azo dyes used are mixtures of dyes including other additives such as intermediates produced during dye www.elsevier.com/locate/dyepig synthesis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of azo dyes has been shown to occur under anaerobic conditions, particularly in association with intestinal microorganisms (7,48). Several different mechanisms have been proposed for reduction or degradation of azo dyes and similar compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Seshadri and coworkers proposed that biotransformation of azo dyes is a two-step process, in which the azo bond is reduced under anaerobic conditions, producing two aromatic amines, which are then mineralized by aerobic microorganisms (51). In contrast to this proposed process, subsequent research showed that in the presence of readily utilizable cosubstrates, two azo dyes were reduced and decolorized under methanogenic conditions (48), and breakdown products from one azo dye were further mineralized. Due to comparatively low operation costs, use of anaerobic digestion to treat dye wastewater is a cost-effective alternative to the physical and chemical methods commonly used to do this.…”
mentioning
confidence: 99%
“…Unlike sludge, which is highly specific to certain substrates [15], the enrichment cultures can degrade any of the target compounds without a lag, although at variable rates. The different rates of biodegradation of ABA and ASA isomers provide additional proof of the significance of the position of substituents in aromatic compounds for their mineralization by active microbial associations [10,12]. The rate of degradation by the associations remained high from cycle to cycle, not changing after passages.…”
Section: Resultsmentioning
confidence: 99%